1994
DOI: 10.1381/096089294765558476
|View full text |Cite
|
Sign up to set email alerts
|

Staple-line Disruptions in Vertical Banded Gastroplasty Related to Different Stapling Techniques

Abstract: We performed one or more upper G.I. barium single-contrast studies on 125 out of 166 Mason vertical banded gastroplasty (VBG) operated patients (total: 226 X-ray examinations during a 3 month-10 year postoperative period). Forty four patients had a staple-line performed by double application of a 2-row stapler with manual reinforcement (group 1); 12 had a single application of a 4-row stapler with reinforcement (group 2); the last 69 patients had a partition with a 4-row stapler without reinforcement (group 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…77,79,89,90,92,95,[97][98][99][100][101][102][103] Over time, there seems to be slow weight regain, 89,98,[104][105][106] with 50% of the patients maintaining 50% or more EWL at 5 years and 40% EWL at 10 years. 98,104,105 The Mayo Clinic, Rochester, Minn, reported only 26% of the 71 patients maintained an EWL of more than 50% 10 years following VBG. 106 Mason et al 107 reported that the morbidly obese patients operated on with their latest generation of VBG, the VBG5, averaged 200% of ideal body weight preoperatively, 145% at 2 years, 151% at 5 years, and 159% at 10 years.…”
Section: Obesity Surgerymentioning
confidence: 99%
“…77,79,89,90,92,95,[97][98][99][100][101][102][103] Over time, there seems to be slow weight regain, 89,98,[104][105][106] with 50% of the patients maintaining 50% or more EWL at 5 years and 40% EWL at 10 years. 98,104,105 The Mayo Clinic, Rochester, Minn, reported only 26% of the 71 patients maintained an EWL of more than 50% 10 years following VBG. 106 Mason et al 107 reported that the morbidly obese patients operated on with their latest generation of VBG, the VBG5, averaged 200% of ideal body weight preoperatively, 145% at 2 years, 151% at 5 years, and 159% at 10 years.…”
Section: Obesity Surgerymentioning
confidence: 99%